2015
DOI: 10.4081/ripppo.2015.181
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative research in adolescent psychotherapy: attachment and reflective functioning as psychotherapy’s outcomes of an adolescent with anorexia nervosa

Abstract: The aim of this study was to examine both the change in attachment state of mind and mentalization competencies as outcomes of a two-year weekly psychodynamic psychotherapy of a female adolescent with anorexia nervosa. The Attachment Interview for Childhood and Adolescence (AICA) was administered at pre and post-treatment, and coded both with the attachment coding system and the Reflective Functioning (RF) scale. At the pre-treatment, the anorexic adolescent was assessed as insecure dismissing with very low le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
(22 reference statements)
0
8
0
2
Order By: Relevance
“…4 It is also estimated that 10 to 25% of children and adolescents eventually show clinical symptoms. 5 In addition to the clinical manifestations and risk factors related to the manifestations of psychopathology, features in personality disorders diagnosed in adults, 6,7 in patients with depression, 8 schizophrenia, 9 autism spectrum disorders, 10 psychopathy, 11 anxiety, 12 eating disorders 13 and in victims of frequent traumas. 14,15 Children and adolescents who experienced traumatic in organizing a sense of identity.…”
Section: Introductionmentioning
confidence: 99%
“…4 It is also estimated that 10 to 25% of children and adolescents eventually show clinical symptoms. 5 In addition to the clinical manifestations and risk factors related to the manifestations of psychopathology, features in personality disorders diagnosed in adults, 6,7 in patients with depression, 8 schizophrenia, 9 autism spectrum disorders, 10 psychopathy, 11 anxiety, 12 eating disorders 13 and in victims of frequent traumas. 14,15 Children and adolescents who experienced traumatic in organizing a sense of identity.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the quality of attachment states of mind of patients with ED can be clinically relevant, not exclusively with respect to the psychiatric diagnosis, but for providing useful information regarding the patient–psychotherapist relationship, the treatment’s outcomes, the reactions to separation during treatments, and the risks of drop-out (D’Onofrio et al, 2015; Lis et al, 2011). However, the attachment studies on ED reported some methodological and theoretical issues including very small sample size, lack of comparison between AN and BN, lack of non-clinical control samples matched for demographic variables, including mostly only inpatients with highly severe ED, considering only the AAI classifications, without paying attention to continuous AAI scales that can provide relevant clinical information.…”
Section: Introductionmentioning
confidence: 99%
“…Mediante la terapia cognitivo conductual y la terapia interpersonal se debe motivar y asesorar al paciente, para generar cambios en su conducta, a través de habilidades para la vida o también llamadas psicosociales que le permitan la resolución de problemas interpersonales (27,28). No obstante, se debe educar al paciente en cuanto al proceso de su enfermedad, para que mantenga hábitos y estilos de vida saludables que contribuyan al logro de sus objetivos personales y el restablecimiento de su estado nutricional (31,32). Otra estrategia es la terapia familiar, la cual es de gran utilidad, ya que es indispen-sable el compromiso, la motivación, el empoderamiento y la actuación por parte de los padres para cumplir con los objetivos; actitudes que permiten que la enfermera intervenga y eduque, teniendo en cuenta las consecuencias de la enfermedad; igualmente, podrá brindar apoyo psicológico, para reducir los sentimientos de culpa, debido al sufrimiento que soportan.…”
Section: Temática 1 Cuidados De Enfermería Que Modifican La Conducta Alimentariaunclassified
“…Se puede concluir, que las características de los tratamientos con mayor éxito para la anorexia nerviosa son: influir en la familia para que se promuevan cambios de conducta en la etapa inicial del tratamiento; brindar un modelo coherente que sea flexible y adaptable según las necesidades específicas del paciente y su familia; y, finalmente, asegurarse de que la intervención sea brindada por una persona especializada, ya que esto favorece un entorno seguro y confiable, en el que se generen nuevos aprendizajes y conductas en los adolescentes y sus familias (32).…”
Section: Temática 3 Impacto De Las Cuidados De Enfermeríaunclassified